2011
DOI: 10.1002/bsl.1003
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Psychopathic Female: A Prototypicality Analysis of the Comprehensive Assessment of Psychopathic Personality (CAPP) Across Gender

Abstract: Psychopathy in women has been subject to little systematic investigation; no coherent conceptualization of the disorder in women exists. Previous research is constrained by the reliance both on a male conceptualization of psychopathy and on assessment instruments developed, and primarily validated, with men. This study utilized a newly developed, broad, personality-based, and gender-sensitive lexical model of psychopathy, the Comprehensive Assessment of Psychopathic Personality (CAPP). Prototypical analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 32 publications
10
96
1
1
Order By: Relevance
“…3, the symptoms of PPD that are hypothesized to influence the presence and magnitude of these three conditions are outlined. Symptoms were identified from prototypicality studies aimed at identifying the core features of PPD as outlined by the Comprehensive Assessment of Psychopathic Personality (CAPP) conceptual model Hoff et al, 2012;Kreis & Cooke, 2011). Regarding individual propensity, a sense of entitlement and intolerance towards others may provide conceptual grounds for the moralistic component of propensity as described by Wikström and Treiber (2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, the symptoms of PPD that are hypothesized to influence the presence and magnitude of these three conditions are outlined. Symptoms were identified from prototypicality studies aimed at identifying the core features of PPD as outlined by the Comprehensive Assessment of Psychopathic Personality (CAPP) conceptual model Hoff et al, 2012;Kreis & Cooke, 2011). Regarding individual propensity, a sense of entitlement and intolerance towards others may provide conceptual grounds for the moralistic component of propensity as described by Wikström and Treiber (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the PCL: YV is considered the 'gold standard' measure of PPD, perhaps the standard is not set high enough and thus it is necessary to move towards an improved measure of PPD. Results of several prototypicality studies have indicated a much broader conceptualization of PPD than the PCL: YV's 20 items Hoff et al, 2012;Kreis & Cooke, 2011). Being over-inclusive of the symptoms of PPD, rather than assuming that just 20 items comprise this construct, may lead to a fuller understanding of the relationship between PPD and offending.…”
Section: Limitations and Future Researchmentioning
confidence: 94%
“…With respect to the psychopathy construct generally and the last question more specifically, it is important to review earlier research on the prototypicality of different symptoms of psychopathy (see Cooke et al, 2012;Hoff, Rypdal, Mykletun, & Cooke, 2012;Kreis & Cooke, 2011;Kreis, Cooke, Michie, Hoff, & Logan, 2012) and possible profiles of these symptoms related to certain types of criminal offending patterns. These prototypicality studies identified a broad range of interpersonal and affective symptoms, including a lack of attachment, empathy, caring, and commitment towards others, a lack of remorse, emotional depth, and emotional stability across multiple situations, a domineering, antagonistic, insincere, and manipulative interpersonal style that features a focus on self, including entitlement, aggrandizing, and justification, and glibness, garrulousness, and verbosity in interactions with others.…”
Section: Core Personality Features Of Psychopathy and Offending Trajementioning
confidence: 99%
“…These domains are purely conceptual and not meant to imply that the psychopathy construct is comprised of six 'factors.' 7 Prototypicality studies examining the validity of the CAPP generally support all 33 symptoms as important to the psychopathy construct Hoff, Rypdal, Mykletun, & Cooke, 2012;Kreis & Cooke, 2011). The 33 symptoms and their adjectival descriptors as distributed throughout the six domains are outlined in Table 1.…”
Section: Introducing the Capp Description Of Psychopathy To Guide Thementioning
confidence: 99%